Foix-Chavany-Marie Syndrome (Anterior Opercular Syndrome) Case Report - Dahbour, Said; Rasheed, Murad; AL Ryalat, Nosaiba; Tarwnah, Asshar; Hadidy, Azmy (Jordan Medical Journal, 2016)
Foix-Chavany-Marie syndrome is a rare cortico-subcortical suprabulbar or pseudobulbar palsy of the lower cranial nerves 5, 7, 9, 10 and 12. This syndrome consists of anarthria, bilateral volitional paresis of the facial, lingual, pharyngeal, and masticatory muscles bilaterally with preservation of the reflexive, emotional and autonomic innervations of the same muscles. We present the first case report in the Middle East of Foix-Chavany-Marie syndrome.